Introduction to Social Media - Lawson, Cheryl (Open textbook library., 2022)
This book is aimed at managers, business owners, marketing managers, and aspiring social media marketing interns and managers. I will assume that however accomplished in your own field - baker, developer, teacher and that even as successful business owners, you approach the topic of social media marketing as a beginner. Even if you are an avid personal user of social networks, we will treat this book as a guided tour of social media for marketing purposes.